Modeling Heterogeneity in UO2 Nanoparticles Using X‐ray Absorption Spectroscopy. Issue 7 (7th December 2022) - Bang, Shinhyo; Russo, Dominic R.; Knapp, Ashley D.; Straub, Mark D.; Smith, Kurt F.; Booth, Corwin H.; Minasian, Stefan G.; Moreau, Liane M.
Abstract: EXAFS provides the capability to interrogate nanoparticle (NP) structure in atomistic detail without relying on long‐range crystallinity. There is a limitation in that EXAFS provides averaged structural information, making it difficult to separate a small amount of heterogeneous structure from bulk. In this work, models were developed to extract surface‐specific information from conventional EXAFS measurements collected on UO2 NPs of varying size. Specifically, the surface terminating species of UO2 NPs was determined from comparison of coordination numbers with geometric models while the origin of static disorder was interrogated from user‐defined simulations. Results show that the degree of oxygenation on the NP surface does not significantly deviate from bulk surface and that static disorder is highly enhanced in NP surface layers but cannot be attributed to surface relaxation effects alone. The approach described herein has the potential to be adapted to a range of inorganic NP systems to interrogate surface structure. Abstract : Various sizes of UO2 NPs were modeled with user‐defined parameters considering surface termination effect, relaxation, and disorder. The surface coordination of the NPs was backtracked by comparing the EXAFS simulated from the model with actual EXAFS experimental data.